Ketro Tourist Village: Community Empowerment Through the Village Tourism Program Economic Recovery Strategy to Welcome to The G20 Presidency - Ida Musofiana; Aprilia Rizki Saputri (LAW FACULTY UNISSULA, 2022)
There are many benefits and impacts of tourism development and development if it is planned and directed properly. The development of Indonesian tourism as a whole is the result of the work of various parties including the Government, the private sector, and the community. The national tourism development policy is an effort to encourage actors in the tourism sector to achieve the goals outlined and the goals set. This article aims: to explain the concept of Ketro Tourist Village and its implementation strategy. This community service uses a qualitative method with an emphasis on descriptive research. The results of this community service show that the Ketro Tourist Village concept is to encourage actors in the tourism sector in achieving the goals outlined and the goals set, it is believed that the tourism sector is a mainstay sector that can contribute to increasing the country's foreign exchange, both directly and indirectly. And the implementation strategy of Ketro Tourist Village in the implementation of Tourism Development in an area is carried out to spur growth both physically and non-physically. Based on this understanding, it is important that the objectives of the implementation of tourism development, especially in Sragen Regency, include the Arrangement of Tourism Facilities and Infrastructure b). Increase various potentials around the reservoir. c). Development of Tourism Objects by establishing a Home Stay as a Tour Package. Whereas the implementation of Tourism Development in Sragen Regency has had a significant impact on the existence of social changes both in terms of economy and in terms of Social and Cultural aspects.